(untitled) (The Pretoria Student Law Review, 2025)
In Khosa and others v Minister of Defence, the High Court was tasked with assessing whether the use of force by Police and Military personnel was lawful and justifiable in enforcing the COVID-19 Lockdown Regulations. The Court declared that when executing Regulations developed to address the COVID-19 pandemic, law enforcement officers are bound by the Constitution, the law, and international law. Mr Collins Khosa was accused by members of the Police and South African National Defence Force (SANDF) of having violated the Lockdown Regulations. Consequently, Mr Khosa was assaulted in his home by military personnel assigned to enforce the COVID-19 Lockdown Regulations. Hours after the assault Mr Khosa succumbed to his injuries and died. The Court found that the use of force against Mr Khosa was unlawful and violated his fundamental constitutional rights. The court emphasised the significance of protecting constitutional rights, especially during times of a national state of disaster, and emphasised that the Police and Military forces must act within the bounds of the Constitution and respect the rights of all individuals. Additionally, the Court highlighted numerous inflammatory public comments made by the Minister of Defence that impacted the enforcement of the Regulations by law enforcement. The Court specified the measures that the Minister of Defence and Police had to implement to effectively investigate the assault on Mr Khosa and prevent further instances of abuse at the hands of Police and Military personnel enforcing the COVID-19 Lockdown Regulations.